HUBUNGAN AKTIVITAS FISIK DAN STRES DENGAN KEJADIAN TIPE PRE MENSTRUAL SYNDROME (PMS) PADA REMAJA PUTRI DI SEKOLAH TINGGI ILMU KESEHATAN PELITA ILMU DEPOK - Putri Wijaya; Romaulina Sipayung (Universitas Batam, 2022)
The physical symptoms and complaints of PMS are divided into several types, namely PMS Anxiety, Craving, Depression and Hyperhydration. According to Dr. Guy E. Abraham about 80% of women experience PMS Anxiety, 60% PMS Hyperhydration, 40% PMS Craving and 20% Depression. In research conducted in Indonesia, it was found that 23% of adolescents in Indonesia experienced premenstrual syndrome symptoms. The cause of PMS is a combination of various factors, namely hormonal, lifestyle (physical activity), micronutrients, and stress (psychological).This type of analytic observational research with a cross-sectional approach. The sampling technique, namely purposive sampling, consisted of 87 young women who met the criteria. The instrument used was a questionnaire. This study uses the chi square test.Purpose: This study aims to determine the relationship between physical activity and stress with the occurrence of premenstrual syndrome types in young women at the Pelita Ilmu Depok High School of Health Sciences.The results showed that the most common type of Premenstrual Syndrome experienced was Type A (Anxiety) (34.5%), light activity (72.4%), and experiencing stress (71.3%). The test results show that there was no relationship between physical activity and the type of Premenstrual Syndrome, p value = 0.609, while there was a relationship between stress and the type of Premenstrual Syndrome, p value = 0.034. There was no relationship between physical activity and the type of premenstrual syndrome, while there was a relationship between stress and the type of premenstrual syndrome.